2010
DOI: 10.1211/ijpp.18.02.0006
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacists' documentation in patients' hospital health records: issues and educational implications

Abstract: Objectives We aimed to identify potential barriers to hospital pharmacists' documentation in patients' hospital health records, and to explore pharmacists' training needs. Our objectives were to identify the methods used by pharmacists to communicate and document patient care issues, to explore pharmacists' attitudes towards documentation of patient care issues in health records, to identify and examine the factors influencing whether or not pharmacists document their care in health records and to make recomme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
11

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 15 publications
1
13
0
11
Order By: Relevance
“…Importantly, the identified standard care acceptance rate is similar to other Irish studies where a ward-based clinical pharmacy service was also employed 21 22. Reasons for this may include an absence of doctor recognition of the pharmacist's contribution, as previously described in a London hospital, or inferior collaboration and teamwork in ward-based standard care 44. The model of clinical pharmacy service currently provided in the majority of Irish teaching hospitals involves medicines reconciliation at admission 45.…”
Section: Discussionsupporting
confidence: 66%
“…Importantly, the identified standard care acceptance rate is similar to other Irish studies where a ward-based clinical pharmacy service was also employed 21 22. Reasons for this may include an absence of doctor recognition of the pharmacist's contribution, as previously described in a London hospital, or inferior collaboration and teamwork in ward-based standard care 44. The model of clinical pharmacy service currently provided in the majority of Irish teaching hospitals involves medicines reconciliation at admission 45.…”
Section: Discussionsupporting
confidence: 66%
“…The lower frequency of, and delay in, standard care clinical pharmacist's recommendation acceptance demonstrates an inefficiency in standard care. Possible contributing factors include an absence of physician recognition of the pharmacist's contribution, as previously described in a London hospital,61 or inferior collaboration and teamwork in the ward-based model. However, this is countered by the estimation that PACT pharmacists were able to see approximately 70% the volume of patients as the standard service, meaning that PACT is 40% more intensive in terms of clinical pharmacy resource.…”
Section: Discussionmentioning
confidence: 99%
“…The recording of the clinical activities of the pharmacist must compose his routine in any setting and with any service offered. Research studies carried out on the subject found results that reinforce the importance of this practice and describe advantages such as patient safety, promoting the rational use of medicines and providing resources for patient care 22,23 .…”
Section: Discussionmentioning
confidence: 73%
“…In this context, Pullinger & Franklin 22 pointed out that most studies on the documentation of the multidisciplinary team in hospitals did not find records of pharmacists and, of those that were performed, most did not include all information from pharmaceutical care. In addition, even when they knew what, when and how to register in the medical record, most of them presented the need to receive training, as those who were trained, demonstrated accuracy and quality in the documentation.…”
Section: Discussionmentioning
confidence: 99%